Application of TOPSIS an PIV Methods for Multi - Criteria Decision Making in Hard Turning Process - Do Duc Trung (Journal of Machine Engineering)
In this study, TOPSIS and PIV methods were applied for multi-criteria decision making in hard turning process. Experiments have been conducted in accordance with an experimental matrix designed by the Taguchi method with a total of twenty-seven experiments. At each experiment, the values of coolant concentration, nose radius, coolant flow, cutting velocity, feed rate and depth of cut have been changed. Surface roughness, flank wear and roundess error have been selected as output criteria. The weights of criteria have been determined by three methods, inclusive of Equal weight, ROC weight and Entropy weight. The combination of multi-criteria decision-making methods with three weighting methods gives six ranking options of the experiments. The purpose of ranking the experiments is to find the experiment at which the three output parameters are ensured to have the minimum value simultaneously.